Promoting the Wellbeing of Physiotherapy Students on Placement:: The Placement Wellbeing Project. A Pilot Study - Rhodes, Jenna; Gill, Louise; Thoms, Alicia (International Journal of Practice-based Learning in Health and Social Care, 2024)
The current healthcare workforce crisis in the United Kingdom has highlighted the need to equip graduates with the skills to maintain their personal wellbeing whilst working in increasingly pressurised environments. The Placement Wellbeing Project (PWP) is an intervention designed to support the wellbeing of physiotherapy students during studies, while on placement and as they enter the workforce. This action research project used a single group, repeated measures design. Ethical approval was gained from the [redacted] ethics committee. On recruitment, participants were given the Placement Wellbeing Toolkit [toolkit link available but redacted as not anonymous to author or organisation] and took part in a pre-placement peer group discussion and a post-placement de-briefing session. Outcomes were measured using the Placement Coping Scale (PCS) and the General Self-Efficacy Scale. Significant improvements were observed in the total PCS score (Friedman’s test χ2(2) = 19.75, p = 0.000) and all individual items of the PCS from baseline to post-placement. Post hoc analysis detected significant improvements between baseline and pre-placement total PCS scores (p = 0.005). Total GSE scores improved significantly from baseline to final measure (Wilcoxon sum-rank test Z = 2.105, p =.035). To develop a resilient future workforce we need to ensure that students are well prepared for challenges and supported to maintain their wellbeing on placement. The results of this study indicate that physiotherapy students may benefit from interventions to develop positive coping strategies for placement.